2021
DOI: 10.1096/fj.202101104r
|View full text |Cite
|
Sign up to set email alerts
|

Low lysophosphatidylcholine induces skeletal muscle myopathy that is aggravated by high‐fat diet feeding

Abstract: Obesity alters skeletal muscle lipidome and promotes myopathy, but it is unknown whether aberrant muscle lipidome contributes to the reduction in skeletal muscle contractile force-generating capacity. Comprehensive lipidomic analyses of mouse skeletal muscle revealed a very strong positive correlation between the abundance of lysophosphatidylcholine (lyso-PC), a class of lipids that is known to be downregulated with obesity, with maximal tetanic force production. The level of lyso-PC is regulated primarily by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Interestingly, previous studies have found that obesity leads to a reduction in muscle lysoPC 30 . Additionally, in skeletal muscle, LysoPC is mainly regulated by LPCAT3, which is acylated to produce PC, and consistent with this finding, lysoPC is reduced when skeletal muscle LPCAT3 is overexpressed 53 . Thus, we suggest that LPCAT3 may be closely associated with the development of skeletal muscle myopathy through the regulation of lysoPC expression.…”
Section: Role Of Lpcat3 In Different Diseasessupporting
confidence: 76%
“…Interestingly, previous studies have found that obesity leads to a reduction in muscle lysoPC 30 . Additionally, in skeletal muscle, LysoPC is mainly regulated by LPCAT3, which is acylated to produce PC, and consistent with this finding, lysoPC is reduced when skeletal muscle LPCAT3 is overexpressed 53 . Thus, we suggest that LPCAT3 may be closely associated with the development of skeletal muscle myopathy through the regulation of lysoPC expression.…”
Section: Role Of Lpcat3 In Different Diseasessupporting
confidence: 76%
“…GPx4 primarily neutralizes LOOH but it also exhibits some activity towards other peroxides [19]. To confirm that the effects of GPx4 deletion to promote atrophy is specific to LOOH, we diminished the ability of cells to incorporate PUFAs into phospholipids by deleting lysophosphatidylcholine acyltransferase 3 (LPCAT3) [2022]. LPCAT3 is an enzyme of Lands cycle that preferentially acylates lysophospholipids with PUFAs, and thus an essential component of ferroptosis [13].…”
Section: Resultsmentioning
confidence: 99%
“…16 To confirm that the effects of GPx4 deletion to promote atrophy is specific to LOOH, we diminished the ability of cells to incorporate polyunsaturated fatty acids (PUFAs) into phospholipids by deleting lysophosphatidylcholine acyltransferase 3 (LPCAT3). [17][18][19] LPCAT3 is an enzyme of Lands cycle that preferentially acylates lysophospholipids with PUFAs, and thus an essential component of ferroptosis 10 . Indeed, LPCAT3 KD rescued the increase in 4-HNE induced by GPx4 KD (Fig.…”
mentioning
confidence: 99%
“…Based on previous studies, we measured CSA of VMO at 5 mm below the upper pole of the patella, the upper pole of the patella, and 5 mm above the upper pole of the patella, in order to compare the change of the CSA of VMO of the same part before surgery and at follow-up. Studies had confirmed that the CSA of muscles was related to the maximum contractility of muscles [ 47 ]. The VMO was a very important dynamic stabilizing device for the inner side of the patella.…”
Section: Discussionmentioning
confidence: 99%